If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 3 + -6n = 13 Reorder the terms: 3 + n + -6n = 13 Combine like terms: n + -6n = -5n 3 + -5n = 13 Solving 3 + -5n = 13 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5n = 13 + -3 Combine like terms: 3 + -3 = 0 0 + -5n = 13 + -3 -5n = 13 + -3 Combine like terms: 13 + -3 = 10 -5n = 10 Divide each side by '-5'. n = -2 Simplifying n = -2
| x^2+0x-20=0 | | -11=x/4-10 | | 5x^2+2x=80 | | 18+-6= | | 1/3(.33)+2=1 | | 6.5+x=42.25 | | (2/3x)-8=(5/6x) | | 1/3x+2=1 | | (-3m^4)(6m^2)(-4m^5)= | | 1/2x+2=12 | | 5=15-4x | | 5.0(x-7.0)=-25(x-10.0) | | Y=16x-7 | | -2[4-(3b+2)]=4-2(3b+7) | | 4_1/3-1_3/5 | | 15a-(12a-(3a+5))= | | -28=-17+a | | 2(4x+2)-8=2(5x+2)-3 | | 2/3(2/3m-2/3)= | | 5x^2-43x+78= | | 1+5(x-8)=2-(x-5) | | X^2+8x=4y-8 | | 12-2x=-6 | | 4(1/2t-5)= | | 4+7(2x+1)=81 | | 7x-(3x+4)=5x-50 | | x-.1x=27 | | 6/16=d/12 | | Y=2x+3y+4+10 | | .10x-x=27 | | 7x+7=x-1 | | .1x-x=27 |